2016
DOI: 10.1128/jvi.02332-15
|View full text |Cite
|
Sign up to set email alerts
|

H1N1 Swine Influenza Viruses Differ from Avian Precursors by a Higher pH Optimum of Membrane Fusion

Abstract: The H1N1 Eurasian avian-like swine (EAsw) influenza viruses originated from an avian H1N1 virus. To characterize potential changes in the membrane fusion activity of the hemagglutinin (HA) during avian-to-swine adaptation of the virus, we studied EAsw viruses isolated in the first years of their circulation in pigs and closely related contemporary H1N1 viruses of wild aquatic birds. Compared to the avian viruses, the swine viruses were less sensitive to neutralization by lysosomotropic agent NH 4 Cl in MDCK ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 75 publications
(92 reference statements)
3
39
0
1
Order By: Relevance
“…To characterize membrane fusion properties of the recombinant IAVs, we determined the pHs at which the viral HAs underwent an acid-induced conformational transition (pH 50-HA ) and at which the virus lost infectivity owing to acid-induced inactivation of the HA (pH 50-inact ). In addition, we compared levels of inhibition of viral infection by the lysosomotropic agent ammonium chloride, which counteracts the acidification of endosomes and lysosomes; a higher sensitivity to NH 4 Cl reflected a viral requirement for a lower pH during fusion and/or uncoating (24). Collectively, these three assays indicated that the HAs of Mem-H1N1 and the two duck IAVs, mal-H1N1 and mal-H2N2, underwent conformational transition and mediated membrane fusion at a lower pH than the HAs of VN-H5N1 and Sh-H7N9 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To characterize membrane fusion properties of the recombinant IAVs, we determined the pHs at which the viral HAs underwent an acid-induced conformational transition (pH 50-HA ) and at which the virus lost infectivity owing to acid-induced inactivation of the HA (pH 50-inact ). In addition, we compared levels of inhibition of viral infection by the lysosomotropic agent ammonium chloride, which counteracts the acidification of endosomes and lysosomes; a higher sensitivity to NH 4 Cl reflected a viral requirement for a lower pH during fusion and/or uncoating (24). Collectively, these three assays indicated that the HAs of Mem-H1N1 and the two duck IAVs, mal-H1N1 and mal-H2N2, underwent conformational transition and mediated membrane fusion at a lower pH than the HAs of VN-H5N1 and Sh-H7N9 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The pH optimum of HA-mediated fusion of avian and mammalian IAVs varies depending on the host species and the history of virus evolution, and our study, for the first time, demonstrates that this variation influences viral sensitivity to IFN and IFITMs. Among different IAVs, human viruses typically have the lowest fusion pH optimum (from 5.0 to 5.4), whereas swine viruses and viruses of gallinaceous poultry, including high-and low-pathogenic IAVs of the H5 and H7 subtypes, display relatively high fusion pH optima (5.6 to 6.0) (22,24,(34)(35)(36)(37)(38)(39). IAVs isolated from wild aquatic birds appear to be particularly variable with respect to the fusion pH optimum (from 5.0 to 6.0), although available data are limited (22-24, 37, 38).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations